PENDAMPINGAN PENGUATAN KEMAMPUAN LITERASI DAN NUMERASI PADA SISWA SEKOLAH DASAR DI KECAMATAN KRAS KABUPATEN KEDIRI - Ria Fajrin Rizqy Ana Ria; Nourma Oktaviarini (Universitas PGRI Adi Buana Surabaya, 2023)
Literacy and numeracy are central to quality learning in all phases of education and curricula. Literacy and numeracy skills contribute to developing the capacity of individuals as global citizens, so that they can contribute productively to society. Students' literacy and numeracy skills are still relatively low. This is caused by children's lack of motivation to learn and try to solve their own problems. The difficulties faced by children in solving problems include difficulties in finding the essence of a text, solving basic operation problems such as multiplication and division, and difficulties in making mathematical models to solve problems related to everyday life. The objectives of the PKM are (1) to provide assistance to students to have high learning motivation with interesting learning activities applied by teachers, (2) to provide assistance to students by applying game activities to learning activities so as to improve literacy and numeracy, (3) to provide socialization to teachers so that they can develop literacy and numeracy so that they can be applied to students optimally. The method used consists of the observation stage, program preparation, and core implementation. The results of the activity show that PKM activities regarding literacy and numeracy assistance to students and teachers have been carried out well, smoothly, and the objectives of the activity have been achieved.